INFESTASI PENGGEREK BUAH KAKAO KEDALAM PERKEBUNAN KAKAO DI KAWASAN KERKAP, BENGKULU UTARA DAN PENGENDALIANNYA - Teddy Suparno . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2001)
Infestation of cocoa pod borer into cacao plantation in kerkap area, north bengkulu and their control. Cocoa pod borer (CPB), Conopomorpha cramerella Snellen, has known as a primary pest on cacao plantation and caused much yield loss. This pest was newly infest into cacao plantation in Bengkulu Province. Objective of the research was to know infestation of CPB into Cacao Plantation in Kerkap area, North Bengkulu. The result showed that all location on cacao plantation area at Kerkap area was gain infestation by cocoa pod borer except the Cacao Plantation at Serumbung Village. Their attack on all plant population was in range between 0.01 and 0.23%, while in produced plant population was in range between 0.20 and 3.06%. The control could be apply are early pick up the pods, used the resistant clones for juvenilization, and spraying by synthetic.